PENDAMPINGAN BUDAYA LITERASI DI ERA COVID 19 PADA ANAK-ANAK DI RUMAH SINGGAH AL-MA’UN KOTA BENGKULU - Yanti Paulina; St Asiyah; Jelita Zakaria; Ira Yuniati (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
The implementation of the Tridarma of Higher Education in the field of Community Service can be carried out by establishing cooperation between universities and certain agencies, both public and private. One form of activity that can be carried out is to provide counseling to children at the Al-Maun shelter, Bengkulu City. This activity is carried out in order to foster a culture of literacy in Indonesian children. The method used in this service is a community approach method, by inviting or motivating children to be able to improve literacy culture, especially reading and writing culture in children's daily lives. The activity steps include: 1) planning; 2) preparing extension materials; and 3) delivering materials with a view to motivating and cultivating a culture of literacy in children at the Al-Maun shelter in Bengkulu City. From the implementation of these activities, it can be concluded that: 1) children get information/knowledge about the importance of literacy culture, especially reading and writing culture and 2) children are motivated to apply Literacy culture in their daily lives.